A internacionalização da agricultura brasileira na transição entre o século XX e XXI - Corte, Tiago Dalla (2015)
This study seeks to apply the theoretical and conceptual contributions of regional history to discuss the internationalization process of Brazilian agriculture. Addresses, initially, the discussion about the nature of the region, its relation to the totality and the definition of historical sources necessary for research. Based on the biases of the possible meanings for the construction of a definition for the region studied, the research conducted focuses on the issue of Regional History, highlighting the need for inclusion of the discussion on the conceptual dimension of the issue of globalization. So, if approached, from a historical point of view, the assumptions regarding the issue of internationalization of Brazilian agriculture in the course of the twentieth century to the twenty-first on a macro scale. From then on, we investigated the determining factors for the internationalization process of Brazilian agriculture to face situations of transition period that occurred in the 1990's through the relevance of agriculture internationalization movement, from which the industry has to be characterized as one of the most dynamic of the Brazilian economy, which justifies the study. In his analysis, arise some questions about the Brazilian economic environment and the impact of their reforms on the sector as well as on the influence of the acceleration of the globalization process of the internationalization process. In this search, carried out the study through dialogue with a number of statistical data, based on suitable reference, aiming to outline the current economic environment during the period of the internationalization process and need temporality of short-term disruptions. Still, the importance of this study is the analysis and confrontation of historical sources as the conventions of Regional History. Wanted thus identify the determining factor, ie the fundamental element for the consolidation of that process, presenting the increase in international prices and, consequently, the final producer price as the determining factor for agriculture internationalization Brazilian. However, it should be noted that the affirmative result for the scenario where the growth and support of agricultural production in Brazil was simply a response to the reagents prices due to considerable changes in global demand for soy products, does not represent a simplification the chain of events in the sector. Thus, the research presents reflections on the fundamental categories for understanding the historical processes at the regional level, allowing isolate clearly fluctuations and process variations, coating with greater security the conclusions reached.